Pelestarian Wayang Wong di Griya Penida, Desa Batuagung, Kecamatan Jembrana, Kabupaten Jembrana, Bali - Laksmi, Ida Ayu Rara Meswara; Laksmiwati, Ida Ayu Alit; Wedasantara, Ida Bagus Oka (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
Wayang w ong is a mask and shadow puppet performance art in which the performers are humans. This art form holds a deep connection with religious spirituality, such as the Ramayana Wayang Wong at Griya Penida, located in Batuagung Village, Jembrana District, Jembrana Regency. The ancestors of Griya Penida brought wayang wong along with the establishment of Griya Penida around the year 1800. Griya Penida has made efforts to maintain the sacredness and continuity of wayang wong , supported by the entire people of Batuagung Villag e . Therefore, this research aims to describe the role of Griya Penida and analyze the function and meaning of wayang wong for Griya Penida and the Batuagung Village community. This research uses observation, interview, and document study techniques. This research also uses a qualitative method with an emphasis on interpretative description. The results of this study explain the forms of preservation carried out by Griya Penida as the main caretaker and the participation of the Batuagung Village community in maintaining the sacredness and continuity of wayang wong . This research also reveals the functions and meanings contained in wayang wong art.